Mądrość pośredniczką wzajemnej miłości Boga i człowieka (Syr 4,11-19) - Piwowar, Andrzej (Verbum Vitae, 2013)
Verb agapaō (to love) occurs only 23 times in the Book of Ben Sira (the verb fileō, instead, does not occur even once!). In the instruction of Wisdom in Sir 4:11-19 it appears as many as four times. It does not seem to be accidental. The analysis of the text carried out in the present article shows that Wisdom functions as a mediator between God and humans. It is Wisdom that leads human being to God, and it is through her mediation that humans receive the gifts that they deserve on the basis of their attitude toward Wisdom and toward the Lord. The first part of the examined passage (vv. 12-16; verse 11 constitutes an introduction), shows a refined theological and poetic structure. The verses 12-14 constitute the first section that focuses on the love of Wisdom and God. The second section (vv. 14a-16) focuses on one’s dedication to Wisdom and, through her mediation, to God. The focal point of the analyzed text can be found in v. 14b: “the Lord loves those who love her”. In v. 17 we read about the test, to which Wisdom put her disciples in order to ascertain their faithfulness and dedication. The last two verses reveal the results of this trial: first positives and then negatives. Wisdom in Sir 4:11-19 appears to be a reliable guide on the way to God. It is Wisdom that introduces her disciples into the close relationship with God. She is a Divine Educator, bringing up human beings in order that they could fully meet God and remain in God’s love.